The Influence of the Adventure Picture Storybook of Petualangan Si Kancil on Reading Comprehension and Reading Motivation Based on Gender - Tundreng, Syarifuddin; Supratman, Supratman (EduBasic Journal: Jurnal Pendidikan Dasar, 2024)
This study aims to examine the influence of the use of the Petualangan si Kancil picture storybook on reading comprehension and motivation among ninth-grade students in the Tanggetada sub-district, Kolaka Regency, with a focus on gender differences. The quantitative design quasi-experimental scheme was used by nonrandomized control, pretest, and posttest design with 54 students divided into an experimental group (27 students) and a control group (27 students). The experimental class used a picture storybook of Petualangan Si Kancil and the control class used the 2013 curriculum book. The experimental class consists of 11 male and 16 female genders, while the control class consists of 10 male and 17 female genders. The instrument used was a written test questionnaire. Data were collected through pretest and posttest measures of reading skills and motivation and analyzed using an Independent sample-t test, with pre-requisite tests (Normality, Homogeneity, and Hypothesis testing) conducted to ensure validity. Results indicate that the picture storybook significantly improves both reading comprehension and motivation, with greater gains observed in the experimental group compared to the control group. Gender-based analysis revealed notable differences, emphasizing the importance of considering gender in educational interventions. These findings suggest that integrating storybooks into the curriculum can support language development, emotional regulation, and memory skills, providing practical implications for educators. Future research should explore the long-term effects of storybooks on student learning across different contexts.